Analisis Laporan Ikhtisar Realisasi Anggaran Untuk Menilai Pencapaian Kinerja Keuangan Pada Kantor Pemerintahan Dinas Lingkungan Hidup Provinsi Sumatera Utara - Dewi, Khadijah Dinda Putri; Lubis, Arnida Wahyuni (Lembaga Riset Ilmiah, 2022)
Budget Realization Report is a report that describes the realization of income, expenditure and financing for a period. Financial performance is a performance measure that uses financial indicators. This study aims to assess the financial performance of the North Sumatra Province Environmental Service Government Office for the 2018-2021 period by using the analysis of the Revenue Budget Variance Analysis, the Decentralization Degree Ratio, the Effectiveness Ratio of Regional Original Revenue, the Regional Expenditure Efficiency Ratio, and the Regional Expenditure Harmony Ratio. This research method uses a quantitative descriptive approach. The analysis method is carried out by assessing or measuring local government financial performance which is measured based on: Income Variance Analysis, Decentralization Degree Ratio, Regional Expenditure Efficiency Ratio, Effectiveness Ratio of Regional Original Revenue, Regional Expenditure Harmony Ratio. The results of research on financial performance at the North Sumatra Province Environmental Service show that 1) Realization of the revenue budget in 2021 is unfavorable but is good if viewed from the whole during the 2018-2021 period. 2) from the Decentralization Degree, showing a ratio of 100%, it can be concluded that the ratio is classified as very good. 3) Regional Expenditure Financial Performance with an average percentage ratio of 90.15% which is on a less efficient interval scale. 4) The PAD Effectiveness Ratio is said to be effective with an average percentage ratio of 120.43% which is included in the very Effective criteria. 5) Shopping Harmony can be concluded that the average percentage ratio is 83,02%.